Phosphorus forms and adsorption capacity in Jambu soil series - Zainal, Syaffaf A'liah (2015)
Phosphorus is often the most limiting plant nutrient, especially in tropical soils. Total P content in Malaysian sandy soil is hundred times lower than the other mineral soils. A study was conducted to study the forms of phosphorus and phosphorus adsorption capacity in the different horizons of Jambu soil series. Sandy soil of Jambu soil series were collected from Merang, Terengganu by Roslan et al.(2010) at different depths which were 0-15cm, 15-30cm, 30-45cm and 45-60cm. The soils were determined for the total P, available P, organic and inorganic P, and P adsorption capacity. The amount of P varies within the soil depths. Total phosphorus content in 0-15cm, 15-30cm, 30-45cm and 45-60cm depth were 6.42 mg/kg, 6.51mg/kg, 5.5 mg/kg and 5.08 mg/kg, respectively. The available P content increased with increasing soil depths which were 1.99 mg/kg, 2.35 mg/kg, 2.51mg/kg and 3.31 mg/kg. The amount of organic P and inorganic P depends on the amount of total P in the soil. The amount of inorganic P was higher than the amount of organic P. Based on adsorption coefficient (Kf value) obtained from Freundlich adsorption isotherm, the highest phosphorus adsorption was at depth 0-15cm, followed by 15-30cm, 30-45cm and 45-60cm.